Metabotropic Glutamate Receptors Modulate Periaqueductal Grey Descending Analgesic System - Palazzo, E.; de Novellis, V.; Marabese, I.; Rossi, F.; Maione, S. (Central Nervous System Agents in Medicinal Chemistry, 2007)
Metabotropic glutamate receptors (mGluRs) are a family of G-protein-coupled receptors which play an important role in the modulation of nociception transmission and plasticity [1,2]. In this review we will consider the control of supraspinal nociception by mGluR ligands in several animal models of pain through behavioural and biochemical approaches. More specifically, we will focus our attention on the mGluRs of the midbrain periaqueductal gray (PAG), which has been recognized as an antinociceptive area since 1969. The multiplicity of responses associated with mGluR stimulation is complicated by the localization of these receptors on a variety of pre- and postsynaptic elements of either glutamate, GABA and non-GABA containing neurons that characterize the PAG circuitry. In particular, excitatory-postsynaptic group I mGlu1/5 subtype receptors produce a preferential activation of descending excitatory antinociceptive pathways at the PAG level, while group III mGlu8 receptors modulate the release of glutamate and GABA conversely. Indeed, selective stimulation of mGlu8 receptors generates an increase in glutamate and a decrease in γ-aminobutyric acid (GABA) extracellular levels. These data, together with the evidence that these receptors are present presynaptically on both symmetrical and asymmetrical synapses, justify that their stimulation relieves hyperalgesia in inflammatory pain. Unlike mGlu8, the mGlu7 receptors in the PAG inhibit antinociception via negative modulation of glutamate release, as they seem expressed mainly on asymmetrical synapses. In this review we aim to illustrate the role of mGluRs in controlling nociceptive processes, as well as their interaction with other neurotransmitters within the PAG, in the hope that further findings in this field will pave the way for the development of useful new agents in pain therapy.
Keywords: antinociceptive descending pathway